Legal trends in the new millennium. Latin America. The 2030 agenda - Sánchez Pinedo , Luz Doris (2025)
Humanity is in crisis and it is necessary to build new paradigms of human development, less mechanistic and more human, supportive, aware of what poverty, hunger, inequality, armed conflicts, violence, displacement, terrorism, climate change, diseases, the adverse impacts of technology, corruption and the lack of identity with indigenous peoples. The COVID-19 pandemic and the triple crisis of climate change, the loss of biodiversity, the lack of solid waste management, the high debts of many developing countries that prevent them from assuming commitments to the World Development Goals. Agenda 2030 (SDG), which is why at this point (2015-2024) and halfway to the deadline for this Agenda, the SDG Progress Report, Special Edition, shows us that more than 50% of the goals are fragile and vulnerable, insufficient, 30% stagnated or regressed. Therefore, it is our objective to carry out, based on said report, a systematic review that answers the questions: what are the legal trends facing the new millennium and the SDGs in Latin America? What is the situation of compliance with the SDGs of the new millennium in Latin America? Is sustainable development a credible paradigm? What is the cost to developing countries of not investing in meeting the SDGs? Does the fact that the 2030 Agenda has not met its goals mean that it has failed? What are the legal trends regarding the SDGs in the new millennium in Latin America? The methodology we use is to review explicit UN reports on the current situation of the SDG goals and other reports.